Flowable sulfur template induced fully interconnected pore structures in graphene artefacts towards high volumetric potassium storage. (June 2020) - Han, Junwei; Zhang, Chen; Kong, Debin; He, Xinzi; Xiao, Jing; Chen, Fanqi; Tao, Ying; Wan, Ying; Yang, Quan-Hong
Abstract: Graphite intercalation compounds are promising anode materials for potassium-ion batteries, but still have problems of sluggish kinetics and a large volume expansion upon potassiation. Porous carbons with a large ion-accessible area used as anode materials can have a high gravimetric capacity and structural stability. However, to avoid a low volumetric performance in porous carbons, an electrode must have both a high density and fast ion-transport channels and these pose stringent requirements for the pore structure. Here we use a flowable sulfur template to produce continually- and precisely-tunable pores in three-dimensional graphene assemblies. During capillary drying of graphene hydrogel, sulfur accompanied with the shrinking graphene sheets controls the formation of pores with precise sizes by tuning the usage. The pores formed are open and interlinked due to the existence of a flowable sulfur template in the graphene network. This obtained graphene-assembly with well-controlled interconnected pores is used as potassium-ion battery anodes and gives a stable cycling performance (500 cycles) and an ultrahigh volumetric capacity. Graphical abstract: Image 1 Highlights: Flowable templating for synthesis of porous carbons with fully interconnected texture. Sulfur as a flowable and continuous template to tune capillary shrinkage of graphene artefact. Shape and size of pore structure including pore connections solely dependent on sulfur usage. Graphene-built porous carbons with fast ion transport and large ion storage for batteries. Ultrahigh volumetric potassium storage with an ultralong life over 500 cycles.